REMOTE SENSING IMAGERY AND GIS FOR MONITORING THE PYROCLASTIC MATERIAL OF MOUNT SINABUNG - Setiawan, Cahyadi; Muzani, Muzani; Warnadi, Warnadi; A'Rachman, Fauzi Ramadhoan; Qismaraga, Qismaraga; Ermalia, Ermalia (Forum Geografi, 2019)
The purpose of this study was to determine the extent of changes in land cover around the Mount Sinabung area after the 2009-2019 eruption by monitoring through remote sensing imagery and GIS. The method used in this research is descriptive quantitative. The technique of data collection used document study techniques by collecting Landsat images are among the widely used satellite remote sensing data and their spectral, spatial and temporal resolution made them useful input for mapping and planning projects (Sadidy et al. 1981). Changes in land cover that occurred around the Mount Sinabung area were dominated by pyroclastic material due to eruption. In addition, changes in land cover also occur due to the abandonment of potential lands, such as local residents who work in the plantation sector are forced to leave that, so they eventually turn into shrubs. The direction of the dominant pyroclastic material slides was directed towards the east-south and southeast of Mount Sinabung, where the area was dominated by the plantation sector. The impact of the eruption of Mount Sinabung was directly and indirectly. The total land cover changes due to pyroclastic material in 2010 was an area of 26.27 Ha, in 2014 it was 475.82 Ha, 2017 was 1339.75 Ha, and 2019 was 1196.11 Ha.